Cultural prejudice on the speaking skill of students (Cadernos de Linguagem e Sociedade, 2022)
Considering the vital role of language teachers in combatting cultural prejudice in the classroom, this study aimed to explore the lived experiences of language teachers when cultural lenses affect their perception of students' speaking skills and cull out techniques in reducing cultural prejudice from their experiences. With phenomenology as its research design, Senior High School language teachers were interviewed, and their responses were transcribed, analyzed, and thematized. Two themes emerged reflecting the cultural prejudices of language teachers in the speaking skills of students – Fossilized Regional Defects and Low Communicative Delivery, and two cultural prejudice reduction strategies materialized – Maximize Profiling Strategies and Respecting Cultural Differences. This study concludes that reflecting on one'